Fractional Integral Operator Associated with the I-Functions (Journal of Mathematical Modeling and Fractional Calculus, 2025)
In this paper we have evaluated certain fractional integral operators associated with Saxenas I-function using the operators of fractional integration. The results obtained are of general character and are reduced to the known results on specializing the parameters. By leveraging the properties of fractional calculus, we investigate new integral transforms involving in this function. We present novel results that extend the existing theory and provide a framework for solving complex integral operators in broadening the scope in this function. These results have potential applications in various fields such as astrophysics, engineering, and applied mathematics, where the I-function and fractional calculus play a crucial role
Keywords: Fractional Integral operators and I-function